Study of the Axiology Values of Pesantren - Muhammad Khoirul Huda; Betty Mauli Rosa Bustam (The Institute of Research and Service Community IPMAFA Pati, 2023)
Philosophy on life has fulfilled and influenced almost every lifeline man. No, except likewise with Axiology and related values with Pesantren, this study for know change values behavior students going outside Pesantren. This research use approach qualitative with method studies library research with type studies case. This study sourced from books and articles discussing a change in value in the Pesantren. The result of the study has shown a number of already values there is since formerly still something preserved inside Pesantren, like case respect more old and love more young, dressed polite, cooperation. The study found that values inside axiology Pesantren no forever can be maintained when they have to go out from the Pesantren like not wearing hijab, like steal, hard for getting along with the public. Even someone who arrived fell with negative association society.